Influence of velocity fluctuations on the Kelvin‐Helmholtz instability and its associated mass transport. Issue 9 (23rd September 2017) - Nykyri, Katariina; Ma, Xuanye; Dimmock, Andrew; Foullon, Claire; Otto, Antonius; Osmane, Adnane
Abstract: Kelvin‐Helmholtz instability (KHI) and associated magnetic reconnection and diffusion processes provide plasma transport from solar wind into the magnetosphere. The efficiency of this transport depends on the magnetosheath and magnetospheric plasma and field properties at the vicinity of the magnetopause. Our recent statistical study using data from the Time History of Events and Macroscale Interactions during Substorms spacecraft indicates that the amplitude of the magnetosheath velocity fluctuations perpendicular to the magnetopause can be substantial. We have performed a series of local macroscale 2.5‐dimensional magnetohydrodynamic simulations of the KHI during strongly northward interplanetary magnetic field and with the initial plasma parameters typical to the dayside magnetopause by perturbing the initial equilibrium with time‐dependent perpendicular velocity field fluctuations. The effect of the single‐mode and multimode seed spectrums at different frequencies and amplitudes is studied. The plasma transport in Kelvin‐Helmholtz vortices is quantified. The results show that when large‐amplitude, low‐frequency seed velocity fluctuations exist in the magnetosheath, the resulting KH waves grow faster, get larger in size, and can transport more plasma through magnetic boundary, resulting in diffusion coefficient of the order 10 9  m 2 /s. The relevance of these findings to the solar wind‐magnetosphere coupling is discussed. Plain Language Summary: Solar wind is magnetized plasma that couples to the near‐Earth magnetic environment due processes that occur at the boundary of the Earth's magnetic shield (the magnetopause) and shocked solar wind plasma (magnetosheath). Solar wind properties are highly variable, and coupling efficiency depends on these solar wind and resulting magnetosheath properties. Giant plasma waves, some 20, 000–40, 000 km in wavelength (so called Kelvin‐Helmholtz waves), can be excited at the magnetopause by velocity shear. Like surfer waves in the ocean, these waves can break the Earth's magnetic shield and carry solar wind plasma through this magnetic barrier. The present paper shows that when large‐amplitude, low‐frequency seed velocity fluctuations exist in the magnetosheath, the resulting KH waves grow faster, get larger in size, and can transport more plasma through magnetic boundary. Key Points: The seed spectrum properties of magnetosheath velocity fluctuations have impact on the Kelvin‐Helmholtz instability For larger‐amplitude seed, KHI reaches the nonlinear stage sooner, and plasma transport starts earlier than for the smaller‐amplitude seed Most plasma transport occurs for seed spectrum including the frequency close to theoretical fastest growing KH mode